Epidemiological aspects of leprosy in the State of Maranhão (Research, Society and Development, 2020)
The study aimed to analyze epidemiological data in the period from 2001 to 2017 of leprosy in Maranhão, a chronic infectious disease caused by the bacillus Mycobacterium Leprae, which affects the skin and nerves, in order to raise the debate about the epidemiological situation of the disease in the state of Maranhão, Brazil . The data analyzed were the rates of detection of new cases in the general population and of cases with grade II incapacity in Maranhão. Through linear regression using the Prais-Winsten method, it was possible to identify a decreasing trend in the annual detection rate in the general population and a stationary trend in the detection rate with grade II disability. However, the detection rate of new cases in 2017 was 44.49 cases per 100,000 inhabitants, with a high rate, classifying maranhão as hyper-endemic. The state showed decreasing detection rates in the general population (APC of -2.76; IC95%: -3.50; -2.01) and in patients with grade II physical disability (APC: -0.07; IC95%: -0.15; -0.00). Thus, it is observed that there have been advances in the fight against leprosy in the state, however, better studies on the reliability of the data and greater effort in combating the disease are suggested, given that it still has high rates in Maranhão.